Analisis Kesalahan Mahasiswa pada Mata Kuliah Matematika Terapan Berdasarkan Newmann’s Error Analysis - Fitri Aida Sari (SUPERMAT (JURNAL PENDIDIKAN MATEMATIKA), 2023)
Applied mathematics is a compulsory subject for students of the Civil Engineering Program at the University of Banten Jaya. Every student must graduate from an applied mathematics course, but in reality, there are still many students who experience difficulties in working on the question given. Students make various mistakes in the process of working on the questions so it is important for lecturers in charge of the course to find out the errors that often occur and the factor that cause these errors. This study aims to find out the mistakes made by students in solving problems in applied mathematics courses and the factors that cause these mistakes. This research is a qualitative descriptive study in which the subjects are students in the third semester of the 2022/2023 odd academic year as many as 30 students in the Civil Engineering Study Program, University of Banten Jaya. Data collection techniques used in this study were tests and non-tests. Non-test data collection activities are carried out through observation, interviews, and documentation. The data analysis technique used is qualitative data analysis which consists of data reduction, data presentation, and making conclusions. The results showed that the types of errors that often occur when students work on test questions are at the stage of transformation and process skills which include errors in understanding the questions given, students' conceptual errors, and errors in determining the correct formula to use in solving the questions. Factors that cause errors to occur include students not understanding the questions, students not understanding the concepts of the material provided, students not being thorough in carrying out the calculation process, and a lack of practice in working on various questions.